Perancangan Kurikulum Program Studi Ilmu Lingkungan Berbasis Outcome-Based Education Terintegrasi Nilai Islam di UIN Antasari Banjarmasin - Verlina Intan Wulandari; Lenalda Febriany Santosa; Rizqi I’anatus Sholihah; Basuki Rahman; Krisologus Genesa Ruby Atmadja (Penerbit Widina, Widina Media Utama, 2025)
The Environmental Science Study Program at UIN Antasari Banjarmasin is a new study program oriented towards sustainable environmental management based on Islamic values. The development of an Outcome-Based Education (OBE) curriculum is a strategic effort to produce graduates who are competent, adaptive, and relevant to the needs of the job market. This article aims to examine the development of an OBE based Environmental Science Study Program curriculum that is integrated with Islamic values. The method used is Research and Development (RD) with the ADDIE model including analysis, design, development, implementation, and evaluation. The results of this study produce a curriculum guideline document for the Environmental Science Study Program based on OBE by integrating Islamic values through two approaches, namely: (1) conceptual integration by placing the principle of khalifah fil ardh' as the philosophical foundation of environmental science learning; and (2) integration of collaborative learning activities and community projects. For Islamic Religious Colleges (PTKI), this curriculum development can strengthen the orientation of graduates who not only master science, but also have integrative competencies between science, ethics, and Islamic values.ABSTRAKProgram Studi Ilmu Lingkungan UIN Antasari Banjarmasin merupakan program studi baru yang berorientasi pada pengelolaan lingkungan berkelanjutan berbasis nilai – nilai Islam. Pengembangan kurikulum berbasis Outcome-Based Education (OBE) merupakan upaya strategis untuk menciptakan lulusan yang kompeten, adaptif, dan relevan dengan kebutuhan dunia kerja. Artikel ini bertujuan untuk mengkaji pengembangan kurikulum Prodi Ilmu Lingkungan berbasis OBE yang terintegrasi dengan nilai – nilai Islam. Metode yang digunakan adalah Research and Development (RD) dengan model ADDIE meliputi analisis, perancangan, pengembangan, implementasi, dan evaluasi. Hasil penelitian ini menghasilkan dokumen pedoman kurikulum Program Studi Ilmu Lingkungan berbasis OBE dengan mengintegrasi nilai – nilai Islam melalui dua pendekatan yaitu: (1) integrasi konseptual dengan menempatkan prinsip khalifah fil ardh’ sebagai landasan filosofis pembelajaran ilmu lingkungan; dan (2) integrasi kegiatan pembelajaran kolaboratif serta proyek komunitas. Bagi Perguruan Tinggi Keagamaan Islam (PTKI), pengembangan kurikulum ini dapat memperkuat orientasi lulusan yang tidak hanya menguasai keilmuan, tetapi juga memiliki kompetensi integratif antara sains, etika, dan nilai keislaman.